Identifikasi dan Analisis Faktor Dominan Penyebab Keterlambatan Proyek Konstruksi di Kecamatan Songgon, Banyuwangi - Yasid, Moh; Prasetyo, Yohanes Pracoyo Widi; Sunarko, Sunarko (Sultra Civil Engineering Journal (SCiEJ), 2025)
This study aims to identify the factors causing delays in construction projects in Songgon District, Banyuwangi Regency, and to analyze the influence of each factor on project delays. The research method employed is quantitative, using a descriptive and analytical survey approach. Data were collected through questionnaires distributed to 66 respondents consisting of contractors, supervising consultants, project owners, and material suppliers. Data analysis was conducted using descriptive statistical techniques, Relative Importance Index (RII), Severity Index (SI), and Importance Index (II). The results show that the most dominant factors contributing to delays are difficult access to material transportation, unfavorable weather conditions, and a shortage of skilled labor, which have the highest RII and SI values. The Importance Index (II) analysis indicates that these factors are also considered highly significant in influencing project delays. This study provides important insights into the local factors affecting construction project delays in Eastern Indonesia, particularly in Banyuwangi Regency, and offers recommendations for mitigating delay risks through infrastructure improvements, more realistic planning, and enhancement of skilled labor availability. This research is expected to serve as a reference for contractors, project owners, and related parties in managing construction projects in areas with similar geographical and socio-economic characteristics